2021
DOI: 10.1111/ases.13012
|View full text |Cite
|
Sign up to set email alerts
|

Current Status of Endoscopic Surgery in Japan: The 15th National Survey of Endoscopic Surgery by the Japan Society for Endoscopic Surgery

Abstract: In Japan, the first endoscopic surgery, a laparoscopic cholecystectomy, was performed in 1990. Since then, operative procedures have been standardized, and the safety and efficacy of endoscopic surgery have been evaluated. In accordance with the social acceptance of endoscopic surgery as a less invasive type of surgery, the number of endoscopic procedures performed has increased in all surgical domains. The Japan Society for Endoscopic Surgery (JSES) has played an important role in the development of endoscopi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(38 citation statements)
references
References 10 publications
1
32
0
Order By: Relevance
“…Notably, there were no conversion cases when considering patients who had undergone preceding colorectal surgery via a laparoscopic approach presumably owing to less intraabdominal adhesion [36][37][38]. The number of patients receiving minimally invasive surgery is increasing worldwide [39,40]. This trend will lead to more opportunities for repeated laparoscopic surgery for colorectal lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, there were no conversion cases when considering patients who had undergone preceding colorectal surgery via a laparoscopic approach presumably owing to less intraabdominal adhesion [36][37][38]. The number of patients receiving minimally invasive surgery is increasing worldwide [39,40]. This trend will lead to more opportunities for repeated laparoscopic surgery for colorectal lesions.…”
Section: Discussionmentioning
confidence: 99%
“…The number of laparoscopic procedures for various diseases and organs has been increasing in Japan in recent years [22] . Additionally, the results of the JLSSG0901 study reported at the 94th Annual Meeting of the Japanese Gastric Cancer Association demonstrated non-inferiority of laparoscopic distal gastrectomy to open approaches in advanced gastric cancer in terms of the 5-year recurrence-free survival rate.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the utility of various resection methods for upper gastric SETs was quite different across different countries. LECS was initially developed in Japan, and the number of LECS being performed annually has thus been consistently rising locally since it was covered by Japanese public medical insurance in 2014 44,45 . On the other hand, endoscopic resection has been extensively applied in China and outcomes of different EFTR procedures were reported predominantly from researchers in China.…”
Section: Lecs Versus Endoscopic Resectionmentioning
confidence: 99%
“…LECS was initially developed in Japan, and the number of LECS being performed annually has thus been consistently rising locally since it was covered by Japanese public medical insurance in 2014. 44,45 On the other hand, endoscopic resection has been extensively applied in China and outcomes of different EFTR procedures were reported predominantly from researchers in China. A Chinese consensus guideline was one of the first to support the use of endoscopic resection for upper GI SETs including low-risk GIST.…”
Section: Lecs Versus Endoscopic Resectionmentioning
confidence: 99%